Is e-governance a function of government or media? Some directions for future research and development of electronically mediated citizen participation - Balnaves, Mark; Allen, Matthew (Association of Internet Researchers, 2009)
Citizen participation, enabled by electronic means, grows, in parallel with government's apparent failure to promote it. Organisations such as Getup and Moveon flourish; the BBC announced in 2003 that 'Internet-based political activism is happening...The BBC wants to help a wider audience find their voice by tackling obstacles to greater participation' (http://www.opendemocracy.net). (Kevill, 2003). Such actions echo, perhaps, the enthusiastic adoption of the Internet by activist media groups, particularly Indymedia. This paper presents a response to this situation. It provides a richer account of the contradictory rise of e-government without e-governance, and examines the potential for media-based participatory engagement to complement e-government. It presents two models of the future of electronically mediated citizen engagement: the first involving agonistic relations between government and citizenry, with civic participation occurring outside of government-approved forums; the second involving the intimate linking of governmental transactions to participation by those citizens engaged in them. Finally it will outline mechanisms for researching the capacity of either or both models to sustain effective participation.